Kepatuhan Pedagang Pasar Terhadap Pembayaran Retribusi: Studi Empiris Pada Pasar Antasari Banjarmasin - Rifqi Novriyandana; Fatimatus Zahroh (Jurnal Akuntansi Publik Nusantara, 2024)
Market retribution is a levy charged for the use of market spaces provided by local governments. This study analyzes the influence of knowledge, tariff, market facilities, and retribution regulations on compliance with retribution payments at Antasari Market, Banjarmasin. With a population of 371 traders, the Slovin formula resulted in a sample of 156 traders. Multiple linear regression analysis using SPSS version 25 revealed that knowledge, tariffs, and regulations significantly influence compliance, while market facilities do not.